Coronary Artery Bypass Graft Surgery - Aronow, Wilbert S. (IntechOpen, 2017)
The book Coronary Artery Bypass Graft Surgery is an excellent update for health care professionals, taking care of patients who are being considered for or who have had coronary artery bypass graft surgery. The 8 chapters in this book are all written by experts in their topics. This excellent book provides the practicing physician and other healthcare personnel, who take care of patients with coronary artery disease, new information valuable in care of patients with coronary artery disease.